2012
DOI: 10.4104/pcrj.2012.00011
|View full text |Cite
|
Sign up to set email alerts
|

High costs and burden of illness in acute rhinosinusitis: real-life treatment patterns and outcomes in Swedish primary care

Abstract: Background: Few studies have investigated the impact of acute rhinosinusitis on disease-specific quality of life, and disease costs have not been studied previously in Scandinavia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 21 publications
(33 reference statements)
0
31
0
5
Order By: Relevance
“…Subjects in this study by Stjärne and colleagues reported poor QoL. 6 They noted high rates of pain/discomfort and limitation to usual activities, so understandably they desired symptom relief. But antibiotics are not always beneficial and can cause harm.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…Subjects in this study by Stjärne and colleagues reported poor QoL. 6 They noted high rates of pain/discomfort and limitation to usual activities, so understandably they desired symptom relief. But antibiotics are not always beneficial and can cause harm.…”
mentioning
confidence: 71%
“…Allergy is a risk factor for acute rhinosinusitis 7 and a quarter of the subjects in this paper 6 report having seasonal allergies. This highlights the importance of assessing for the role of allergies.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…8 Data on disease severity, resource use, and HRQoL were collected at the first physician visit and at follow-up 15 (±2) days later. Baseline patient characteristics were similar to those reported for subjects in the clinical study (baseline mean MSS 8.34 and 8.39 and mean age 35 and 45 years in the clinical study and the observational study, respectively).…”
Section: Input Datamentioning
confidence: 99%